2018
DOI: 10.1016/j.yrtph.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tobacco heating product THP1.0. Part 8: Study to determine puffing topography, mouth level exposure and consumption among Japanese users

Abstract: A four-arm study was undertaken in Japan to determine the puffing topography, mouth level exposure and average daily consumption by consumers of the tobacco heating products (THPs): the non-mentholated THP1.0(T), the mentholated THP1.0(M) and a tobacco heating system (THS). The extent of lip blocking of air inlet holes while using THP1.0(T) was also assessed. Groups 1, 2, and 4 included smokers, and group 3 included regular THP users. Smokers of 7-8 mg ISO nicotine free dry particulate matter (NFDPM) non-menth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
3
28
2
Order By: Relevance
“…There were no statistically significant differences seen between Group 1 (smokers) and Group 2 (vapers or dual users), suggesting that a familiarisation period of 5-days was sufficient time to enable collection of www.nature.com/scientificreports www.nature.com/scientificreports/ consumer-representative data. Comparisons between this study and Gee et al 18 highlight the use-behaviour differences between Italian and Japanese consumers of tobacco and nicotine products. Italian smokers using THP1.0(T) were, on average, observed to take more puffs per session (15.4 ± 7.4 vs. 10.9 ± 5.6), lower mean puff volumes (46.6 mL ± 1 6.8 mL vs. 66.7 mL ± 23.7 mL) and longer intervals between puffs (11.1 s ± 5.8 s vs. 7.4 s ± 2.7 s).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…There were no statistically significant differences seen between Group 1 (smokers) and Group 2 (vapers or dual users), suggesting that a familiarisation period of 5-days was sufficient time to enable collection of www.nature.com/scientificreports www.nature.com/scientificreports/ consumer-representative data. Comparisons between this study and Gee et al 18 highlight the use-behaviour differences between Italian and Japanese consumers of tobacco and nicotine products. Italian smokers using THP1.0(T) were, on average, observed to take more puffs per session (15.4 ± 7.4 vs. 10.9 ± 5.6), lower mean puff volumes (46.6 mL ± 1 6.8 mL vs. 66.7 mL ± 23.7 mL) and longer intervals between puffs (11.1 s ± 5.8 s vs. 7.4 s ± 2.7 s).…”
Section: Discussionsupporting
confidence: 56%
“…Generally, the machine puffing regimes used for pre-clinical laboratory measurements were broadly supported by the puffing topography measurements, despite the differences between products. This was further supported for THP1.0(T) where the 95th percentile MLE for optical NFDPM in the actual use study was in line with the mHCI (55 mL puff over 2 s every 30 seconds 29 , with no vent blocking 18 ) machine measured NFDPM yield (Table S4). The average MLE to ACM for IS1.0(T) was also in line with the existing 55/3/30 machine testing regime 30 (Table S5).…”
Section: Central Locationsupporting
confidence: 62%
See 1 more Smart Citation
“…The tobacco industry has performed multiple studies regarding health consequences of HTP use. The results of in vitro and in vivo studies indicate that HTP aerosols have lower toxicity and no new hazards compared to conventional cigarette smoke [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. The results of humanbased studies also suggest that switching from conventional cigarettes to IQOS or glo leads to reductions in exposure to smoke toxicants in a manner comparable to quitting tobacco use [74][75][76][77][78].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 94%
“…Following the manufacturer recommendations, especially proper cleaning of the device after each 20 tobacco sticks seems to be crucial to provide proper thermal regulation and reduce emissions of harmful substances. Most of the research regarding the chemical composition of generated aerosol was carried out on brand new, never used devices [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Independent researchers showed that the use of 1 IQOS tobacco stick left a significant amount of debris, fluid, and fragments of cast-leaf in the device holder [8].…”
Section: Marketing Strategies Of Htp Promotionmentioning
confidence: 99%